What are the Economic Effects of Pandemic Containment Policies? : Evidence from Sweden - Bricco, Jana (IMF Working Papers; Working Paper, 2020)
This paper examines the economic effects of policies to contain Covid-19, by extracting lessons from Sweden's experience during the 'Great Lockdown'. Sweden's approach was less stringent and based more on social responsibility than legal obligations compared to European peers. First, we provide an account of Sweden's strategy and the health outcomes. Second, drawing on a range of data sources and empirical findings, our analysis of the first Covid-19 wave indicates that a less stringent strategy can soften the economic impact initially. These benefits could be eroded subsequently, due to potentially higher infection rates and a prolonged pandemic, but in Sweden's case, the evidence remains mixed in this regard, and it is premature to judge the outcome of Sweden's containment strategy. In addition, the economic effects of the containment strategy also depend on social behavior, demographics and structural features of the economy, such as the degree of export orientation, reliance on global supply chains, and malleability to remote working.